Digitalization Training for Early Childhood Education Teachers' Learning Media through the Smart Media Program in North Lampung (Video, Animation, Educational Games) - Dahlawi Fath; Sri Hasanah; Ahmad Sholihin; Rika Westika; Supriyanti Supriyanti (Amalee: Indonesian Journal of Community Research and Engagement, 2026)
The Smart Media Program in North Lampung was implemented to address low digital literacy and limited use of technology-based learning media among early childhood education (PAUD) teachers. This program aims to improve teachers' digital competence in developing educational videos, simple animations, and child-friendly educational games that align with the characteristics of early childhood learning. The program involved 25 PAUD teachers from institutions under the Harapan Umi Foundation and was implemented over six days through stages of socialization, training, workshops, mentoring, and evaluation. Using a Participatory Action Research (PAR) approach, data were collected through observation, interviews, and documentation. The service results showed that teachers produced 42 digital learning products, including 18 educational videos, 14 simple animations, and 10 interactive educational games, which were directly implemented in classroom learning. The program improved teachers' technical skills, creativity, and confidence while fostering a more engaging, interactive learning environment. Improved focus, participation, and enthusiasm were observed in children, along with strengthened collaboration between teachers. These findings indicate that the Smart Media Program effectively improves the digital literacy and professional competence of PAUD teachers and offers a sustainable model for early childhood teacher development.